The comparison of the effectiveness of shoe flower (Hibiscus rosa-sinensis L.) and roselle flower (Hibiscus sabdariffa L.) infusions as alternative reagents for the examination of Soil Transmitted Helminths (STH) eggs - Acivrida Mega Charisma; Eka Octaviana Rahayu; Farida Anwari (Universitas Nahdlatul Ulama Surabaya, 2024)
Worm infections remain a significant health challenge globally, including in Indonesia, where they continue to contribute to a majority of health issues. Soil-transmitted helminths (STH), particularly intestinal nematode parasites, are predominant in causing these infections. Microscopic examination with 2% eosin staining is a conventional method for diagnosing worm infections. However, exploring alternative staining agents, such as anthocyanin-rich extracts from Hibiscus rosa-sinensis L. (hibiscus flower) and Hibiscus sabdariffa L. (roselle flower), presents a promising avenue. These plants possess anthocyanin compounds, resulting in a captivating red pigment and making them suitable for utilization as natural coloring agents. This study aimed to evaluate the efficacy of hibiscus and roselle infusions as alternative staining reagents for examining STH egg, compared to the standard 2% eosin staining method. Adopting a true experimental design, samples of STH worm egg suspensions were subjected to different concentrations of hibiscus and roselle infusions. The results revealed varying staining outcomes with different concentrations. However, a 1:1 concentration ratio of hibiscus and roselle infusions demonstrated effective staining against STH worm eggs. In conclusion, this research underscores the comparative effectiveness of hibiscus and roselle infusions as alternative staining reagents for STH egg examination, with 2% eosin serving as the control. These findings hold potential implications for improving diagnostic techniques in managing worm infections.